A contemporary examination of workplace learning culture: An ethnomethodology study. (January 2015) - Newton, Jennifer M.; Henderson, Amanda; Jolly, Brian; Greaves, Judith
Summary: Background: Creating and maintaining a sustainable workforce is currently an international concern. Extensive literature suggest that students and staff need to be 'engaged', that is they need to interact with the health team if they are to maximise learning opportunities. Despite many studies since the 1970s into what creates a 'good' learning environment, ongoing issues continue to challenge healthcare organisations and educators. A 'good' learning environment has been an intangible element for many professions as learning is hindered by the complexity of practice and by limitations on practitioners' time available to assist and guide novices. Objectives: This study sought to explore the nature of the learning interactions and experiences in clinical nursing practice that enhance a 'good' workplace learning culture for both nursing students and qualified nurses. Design: An ethnomethodology study. Setting: A range of clinical settings in Victoria and Queensland, Australia. Participants: Students and registered nurses (n = 95). Methods: Fieldwork observations were carried out on student nurses and registered nurses, followed by an individual interview with each participant. An iterative approach to analysis was undertaken; field notes of observations were reviewed, interviews transcribed verbatim and entered into NVivo10. Major themes were then extracted. Results: Three central themes: learning by doing, navigating through communication, and 'entrustability', emerged providing insights into common practices potentially enhancing or detracting from learning in the workplace. Conclusions: Students' and registered nurses' learning is constrained by a myriad of interactions and embedded workplace practices, which can either enhance the individual's opportunities for learning or detract from the richness of affordances that healthcare workplace settings have to offer. Until the culture/or routine practices of the healthcare workplace are challenged, the trust and meaningful communication essential to learning in practice, will be achievable only serendipitously.